Pharmacokinetic characteristics of golidocitinib, a highly selective JAK1 inhibitor, in healthy adult participants - Chen, Kan; Guan, Xiaoduo; Yang, Zhenfan; Zhou, Yue; Liu, Ziyi; Deng, Xueyuan; Liu, Donghong; Hu, Pei; Chen, Rui (Frontiers in Immunology, 2023)
Background: Golidocitinib is an orally available, potent and highly selective JAK (Janus kinase)-1 inhibitor of JAK/STAT3 signaling under clinical development for the treatment of cancer and autoimmune diseases. The objectives of the two reported studies were to investigate the pharmacokinetics (PK), safety, and tolerability of golidocitinib in healthy Chinese participants as compared to those healthy Western participants, as well as the food effect exploration. Methods: Two phase I studies (JACKPOT2 and JACKPOT3) were conducted in USA and China, respectively. In JACKPOT2 study, participants were randomized into placebo or golidocitinib arm in single-ascending dose cohorts (5 - 150 mg) and multiple-ascending dose cohorts (25 - 100 mg, once daily) for 14 days. In the food effect cohort, golidocitinib (50 mg) was administrated shortly after a high-fat meal (fed conditions) as compared to under fasting conditions. In JACKPOT3 study conducted in China, participants were randomized to placebo or golidocitinib arm in single-ascending dose cohorts (25 - 150 mg). Results: Exposure of golidocitinib generally increased in a dose-proportional manner across a dose range of 5 mg to 150 mg (single dose) and 25 mg to 100 mg (once daily). High-fat food did not alter the PK of golidocitinib with statistical significance. Low plasma clearance and extensive volume of distribution characterizes PK of golidoctinib, and long half-life across the dose levels supported once daily dosing. The inter-ethnic difference in primary PK parameters was evaluated. The result suggested slightly higher peak plasma concentrations (Cmax) but comparable area under the plasma concentration-time curve (AUC) was observed in Asian (Chinese) subjects as compared to Caucasian and/or Black subjects, while it was not considered clinically relevant. Golidocitinib was well tolerated without Common Terminology Criteria for Adverse Events (CTCAE) grade 3 or higher drug-related treatment emergent adverse events (TEAE) reported. Conclusion: No noticeable inter-ethnic difference was observed among Asian, Black, and Caucasian healthy subjects in anticipation of the favorable PK properties of golidocitinib. The effect of food on the bioavailability of golidocitinib was minor following a single oral administration of 50 mg. These data guided to use the same dose and regimen for multinational clinical development.